Clarke, Bruce. (2020). Gaian Systems: Lynn Margulis, Neocybernetics, and the End of the Anthropocene - Gough, Noel (Journal of Ecohumanism, 2023)
Clarke, Bruce. (2020). Gaian Systems: Lynn Margulis, Neocybernetics, and the End of the Anthropocene. University of Minnesota Press. ISBN 978-1517909123